Penerapan Collaborative Governance Pusat Informasi Wisata Ngebel Melalui Website Dolanngebel.com - Sindy Novia Ardana; Yusuf Adam Hilman; Robby Darwis Nasution; Bambang Widiyahseno (Politeknik Pariwisata NHI Bandung, 2022)
The Ngebel District Government developed website technology in collaboration with Akedimis to advance the tourism potential sector towards the digital era. The purpose of this study is to describe the collaborative development of the dolanngebel.com website as tourism information on Ngebel's potential. The method used in this study is a qualitative method, the data used can be obtained from observation, in-depth interviews, and documentation. This website was developed to facilitate access for tourists to find Ngebel tourist information through social media. The results of this study in Collaborative Governance resulted in a strategy carried out by the Ngebel District government in collaboration with academics, namely inviting business people to be able to operate websites to increase tourist visitors and carry out promotions through social media regarding the development of the dolanngebel.com website to attract visiting tourists.